The Decay of University Education in Sri Lanka A Rejoinder to the Performance Audit Report of the National Audit Office on Arts Education - Sarvananthan, M. (Social Science Research Network, 2023)
This is a critical analysis of and critical reflections on the Performance Audit Report (PAR) of the National Audit Office on the arts stream education at senior secondary school and university undergraduate level in Sri Lanka. The PAR claims that arts stream education has failed to produce employable graduates because the curriculum is academic oriented rather than skills oriented. This rejoinder to the PAR argues that the university education is failing to produce employable graduates because it is neither academic oriented nor skills oriented due to both institutional decay of the public universities in Sri Lanka as well as the decay of individuals, especially the academic staff, in the public universities in Sri Lanka in the last 50 years or so (1972-2021).
Keywords: Academic/Intellectual Fraud; Higher Education; Plagiarism; Predatory Publications; Public Universities; Sri Lanka